A review on the effects of shoulder diameter to pin diameter (D/d) ratio on friction stir welded aluminium alloys. (2021) - Muthu Vaidyanathan, R.; Sivaraman, N.; Patel, Mahaboob; Woldegioris, Mebratu Markos; Atiso, Tsegaye Alemayehu
Abstract: Friction stir welding is a predominant procedure to bind numerous materials. An optimal parameter is vital to create a better and defect-free weld. The thermomechanical joining methods have a unique advantage, and it needs an appropriate key variable for better joining. Though many parameters control the process, the D/d ratio and rotational speed are the key factors. An aluminium alloy with a similar and dissimilar joint was considered. The association of the D/d ratio of a straight cylindrical pin with rotational speed and welding speed on an aluminium alloy butt joint was studied. In addition to various parameters, the D/d ratio immensely impacts mechanical strength and grain refinement. A shoulder diameter to pin diameter ratio of three significantly increases the tensile strength, joint efficiency, and elongation.